Evaluation of Post-Hemithyroidectomy hypothyroidism (Bangladesh Journal of Otorhinolaryngology, 2020)
Objective: To evaluate the incidence of post-hemithyroidectomy hypothyroidism and identify possible risk factors that indicates which patients require thyroid function monitoring after surgery.Methods: A prospective study of patients with benign, non-toxic thyroid disease undergoing hemithyroidectomy between January 2017 and July 2019 in the Department of Otolaryngology and Head-Neck Surgery, Sir Salimullah Medical College Mitford Hospital, Dhaka. All patients were in euthyroid state preoperatively.Thyroid specimens were examined for pathological diagnosis and thyroid function was evaluated again six weeks after surgery.Results: All had normal preoperative thyroid function. Six weeks after surgery, 10 (22.22%) of the cases developed hypothyroidism (6.66% overt or symptomatic hypothyroidism and 15.56% subclinical hypothyroidism). The mean preoperative TSH level was significantly higher in the hypothyroid group than in the euthyroid group (2.1±1.1 vs 1.3±0.7mIU/L, p